Study of some hematological and biochemical parameter of Friesian crossbred cows in Sulaimanya governorate: Juma FT HamaKhan KM - FT., Juma (The Iraqi Journal of Veterinary Medicine, 2011)
The present study was carried out at Bakrajo field station which belongs to the college of Agriculture University Sulaimanya during the period from the1st of April untill 30th of October 2009.This study include 10 crossbred Friesian cows aged 5-7 years old to study some hematological and biochemical changes during late pregnancy (last three months ) and lactation period (4months).The cows were divided into two groups, the first group included 5 non-pregnant cows used as control group while the second group included 5cows were in the late pregnancy (last three months) and continues to four months of miproduction. Statistically all significant results of blood and biochemical results at (P<0.05). The results showed a significant decreased of the erythrocytes number during late stage of pregnancy and lactation period as comparison with non-pregnant cows. Hemoglobin concentration decreased significantly during 3rd and 4th of lactation in comparison with 7th and 8th months of pregnancy and non pregnant animals ,while PCV showed significant increase during 9th month of pregnancy in comparison with 2nd,3rd and4thmonths of lactation and non- pregnant cows. There were a significant increased in MCV and MCH during pregnancy in comparison with months of lactation, and significantly increase of MCHC at 7th month of pregnancy in comparison with 2nd, 3rd and 4th months of lactation. There were a significant increased of Leukocyte count at the last two months of pregnancy in comparison with non-pregnant animals. In regard to the biochemical changes, there was a significant decreased of glucose concentration at both pregnancy and lactation period in comparison with non-pregnant animals. Total serum cholesterol concentration was significantly increased at the pregnancy and lactation period in comparison with control group, while total serum protein concentration significantly decreased at the 1stmonth of lactation in comparison with 2nd, 3rd and 4th months and control group, concentration of ionized calcium and inorganic phosphorus significantly decreased during last period of pregnancy and lactation period in comparison with non-pregnant cows. In regard to serum enzyme change significant increased in the activity of AST during the second month of lactation in comparison